Role of lung ultrasound in diagnosis of respiratory distress syndrome in pre-term babies (≤32 weeks) - Suhaib, Pirzada M.; Asma Gulzar,; Saqib, Mir N.; Rasool, Sheikh R.; Bhat, Mushtaq A.; Bhat, Mudasir H. (International Journal of Contemporary Pediatrics, 2025)
Background: Respiratory distress syndrome (RDS) is a common problem faced by newborns associated with high mortality and morbidity if not diagnosed and managed in time. The aim of our study was to evaluate the ability of lung ultrasound against chest X-ray in the diagnosis of RDS in pre-term infants born before 32 weeks and to follow up on the response to treatment. Methods: The study was conducted on sixty neonates with gestational age (GA) ≤32 weeks (mean GA 30.3±1.64 weeks) and birth weight appropriate for gestational age (mean birth weight 1,350±310 g) who were admitted to neonatal intensive care unit (ICU) within six hours after birth with respiratory distress. The ling ultrasound (LUS) and chest X-ray findings were compared with the reference standard (i.e., clinical diagnosis) and the patients followed till clinical recovery, normal LUS scans or eventual fatal outcome, whichever was earlier. Results: LUS diagnosed RDS with a sensitivity of 88.1% and specificity of 83.33%, while chest X-ray showed a sensitivity of 90.48% and specificity of 72.22%. Furthermore, an LUS score of 10 predicted RDS well in our study. The disease was mostly limited to the first few days following birth, with normal LUS scan, clinical recovery, or death mostly occurring within the first few days of life with a mean of 5.48±4.2 days. Conclusions: We concluded that lung ultrasound is comparable to a chest X-ray in diagnosing neonatal RDS with a high degree of accuracy while detecting other complications as well. With proper training and expertise, it is likely to replace chest X-ray as the primary modality of choice in diagnosing respiratory diseases, especially in neonates.